Geographical distributions of rhytismataceous fungi on Camellia japonica leaf litter in Japan. (April 2017) - Matsukura, Kimiyo; Hirose, Dai; Kagami, Maiko; Osono, Takashi; Yamaoka, Yuichi
Abstract: Rhytismataceous fungi (Ascomycota) exhibit ligninolytic activities during the initial stages of litter decomposition. We quantitatively investigated the geographical distributions of rhytismataceous fungi on Camellia japonica leaf litter across Japan. We found three rhytismataceous species ( Coccomyces sp., Lophodermium jiangnanense, and a Rhytismataceae sp.) on bleached leaves of C. japonica . The Coccomyces sp. was distributed at all 40 sites investigated. On the other hand, L. jiangnanense was restricted to the southwestern region, and the Rhytismataceae sp. was localized to part of the warm-temperate zone. L. jiangnanense and the Rhytismataceae sp. were more common at sites with higher annual temperatures and greater precipitation. The relative abundance of rhytismataceous fungi revealed that either Coccomyces sp. or L. jiangnanense predominated at all sites, with a distribution related to annual precipitation. These results suggest that the geographical distributions and abundances of rhytismataceous fungi are influenced by climatic conditions. Highlights: Three rhytismataceous species on Camellia japonica leaf litter were quantified. Coccomyces sp. was distributed at all sites investigated. Lophodermium jiangnanense and the Rhytismataceae sp. localized in a part of Japan. The frequencies of them correlated to annual temperatures and annual precipitation. Colony area showed either Coccomyces sp. or L. jiangnanense dominated at each site.